Congestion Control for WebRTC: Standardization Status and Open Issues - Luca De Cicco; Gaetano Carlucci; Saverio Mascolo (IEEE Communications Standards Magazine, 2017)
The WebRTC initiative has achieved impressive results in terms of the gained industrial interest, the penetration of the technology in end-user devices, and the ever growing community of developers. WebRTC is today supported by major mobile platforms and Internet browsers, allowing potentially billions of users to seamlessly establish real-time communication sessions. Among all the functionalities that must be implemented by WebRTC devices, congestion control is particularly important to ensure that the network operates properly while providing a satisfactory user experience. A working group that is focusing on this issue is the IETF RTP Media Congestion Avoidance Techniques (RMCAT), which aims at defining the requirements and designing congestion control algorithms to be used for the transport of real-time media flows over RTP. This article overviews the status of the standardization efforts that are taking place in the RMCAT working group. We discuss the choices involved in the design of media congestion control, the proposed algorithms, and the issues that are considered still open.
Keywords: Traffic congestion; Media; WebRTC; Algorithm design and analysis; Bandwidth; Telecommunication traffic; Real-time systems; Internet